The inactivation of RNase G reduces the Stenotrophomonas maltophilia susceptibility to quinolones by triggering the heat shock response - Bernardini, Alejandra; Corona, Fernando; Dias, Ricardo; Sánchez, Maria B.; Martínez, Jose L. (Frontiers in Microbiology, 2015)
Quinolone resistance is usually due to mutations in the genes encoding bacterial topoisomerases. However different reports have shown that neither clinical quinolone resistant isolates nor in vitro obtained S. maltophilia mutants present mutations in such genes. The mechanisms so far described consist on efflux pumps' overexpression. Our objective is to get information on novel mechanisms of S. maltophilia quinolone resistance. For this purpose, a transposon-insertion mutant library was obtained in S. maltophilia D457.. One mutant presenting reduced susceptibility to nalidixic acid was selected. Inverse PCR showed that the inactivated gene encodes RNase G. Complementation of the mutant with wild-type RNase G allele restored the susceptibility to quinolones. Transcriptomic and real-time RT-PCR analyses showed that several genes encoding heat-shock response proteins were expressed at higher levels in the RNase defective mutant than in the wild-type strain. In agreement with this situation, heat-shock reduces the S. maltophilia susceptibility to quinolone. We can then conclude that the inactivation of the RNase G reduces the susceptibility of S. maltophilia to quinolones, most likely by regulating the expression of heat-shock response genes. Heat-shock induces a transient phenotype of quinolone resistance in S. maltophilia.